2007
DOI: 10.1007/s11259-006-3390-5
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction–Restriction Fragment Length Polymorphism of Mitochondrial 12S rRNA Gene: A Simple Method for Identification of Poultry Meat Species

Abstract: Chicken (Gallus gallus), duck (Anas platyrhynchos), turkey (Meleagris gallopavo), guinea fowl (Numida meleagris) and quail (Coturnix japonica) are the common poultry species consumed as meat throughout the world. In this work, a molecular technique has been developed for identification and differentiation of meat originating from these species. This tool helps in detection of misrepresentation of different poultry meats. The technique involves the extraction of DNA from the given sample, polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 11 publications
(9 reference statements)
0
25
0
Order By: Relevance
“…Earlier workers have also exploited mitochondrial 12S rRNA gene (Prakash et al 2000;Girish et al 2004;Rastogi et al 2004) and mitochondrial cytochrome b gene (Meyer et al 1995;Unseld et al 1995;Hsieh et al 2005) for meat species identification, and it has also been reported that the PCR amplification of mitochondrial 16S rRNA gene has been used for identification of snail species (Abdulmawjood and Buelte, 2002). Earlier also reported that the PCR amplification followed by DNA sequencing can be the best way to identify the species origin of meat from all meat animals (Girish et al 2007). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier workers have also exploited mitochondrial 12S rRNA gene (Prakash et al 2000;Girish et al 2004;Rastogi et al 2004) and mitochondrial cytochrome b gene (Meyer et al 1995;Unseld et al 1995;Hsieh et al 2005) for meat species identification, and it has also been reported that the PCR amplification of mitochondrial 16S rRNA gene has been used for identification of snail species (Abdulmawjood and Buelte, 2002). Earlier also reported that the PCR amplification followed by DNA sequencing can be the best way to identify the species origin of meat from all meat animals (Girish et al 2007). …”
Section: Resultsmentioning
confidence: 99%
“…Identification of buffalo, emu and crocodile species was done by PCR amplification and sequencing of cytochrome b gene (Forrest and Carnegie 1994). Recently, Girish et al (2007) employed partial sequence analysis of 402 bp PCR amplified fragments of cytochrome b gene for identification of animal species in fresh and processed samples of unknown origin. These workers identified the species in unknown samples by the sequence analysis of PCR amplified DNA fragments.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other meat species, there are fewer poultry-specific assays for food authentication and quality control (Stamoulis et al 2010). Most poultry DNA-based assays utilize avian mitochondrial genes and do not have a nuclear DNA quantification component (Dalmasso et al 2004;Girish et al 2007;Stamoulis et al 2010;Kocher et al 1989;Herman 2004;Haunshi et al 2009;Girish et al 2011). The integration of species determination and nuclear DNA quantification into a single assay will streamline downstream genotyping analysis, and improve the quality of the DNA profiles while conserving reagents (Evans et al 2007;Lindquist et al 2011;Kanthaswamy et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Of the few poultry assays developed, most rely on mitochondrial DNA (mtDNA) genes as markers for detection (Girish et al 2007;Haunshi et al 2009;Herman 2001;Soares et al 2010). Since mtDNA occurs in high copy numbers in each cell and is able to withstand degradation and environmental challenges, it is well suited for use in food authentication assays.…”
Section: Introductionmentioning
confidence: 99%
“…The DNA molecule is more stable and the composition of DNA is same in any cell of the individual. Hence, DNA based techniques namely Polymerase Chain Reaction (PCR) and its variants: Restriction Fragment Length Polymorphism (RFLP) (Girish et al 2005); Random Amplified Polymorphic DNA (RAPD) finger printing (Saez et al 2004); DNA Hybridization (Buntjer et al 1999), PCR Sequencing (Girish et al 2007); Arbitrarily Primed-PCR (AP-PCR) (Desmarais et al 1998) and PCR-Single Strand Conformation Polymorphisms (SSCP) (Tejedor et al 2006) and species specific markers (Haunshi et al 2009) have been employed for the identification of various animal species in the recent past. The PCR-based techniques provide high level of specificity, sensitivity, accuracy and precision than the techniques hitherto being used for the purpose of animal species identification.…”
Section: Introductionmentioning
confidence: 99%